A Novel High-Amylose Wheat-Based Functional Cereal Soup (Tarhana) With Low Glycemic Index and High Resistant Starch - Koksel, Hamit; Tekin-Cakmak, Zeynep Hazal; Ozkan, Kubra; Pekacar, Zeynep; Oruc, Sena; Kahraman, Kevser; Sestili, Francesco (Academic Press Ltd- Elsevier Science Ltd, 2024)
This study investigated the potential of high-amylose wheat flour (Svevo-HA) to enhance the dietary profile of tarhana, a traditional Mediterranean fermented cereal yogurt mixture. The moisture content of tarhana powders ranged from 7.81% to 11.64%. Color parameters varied depending on the type of flour used, with Svevo-HA samples demonstrating decreased L* values and increased a* and b* values. Mineral compositions differed significantly among tarhana samples, with higher levels of K, Mg, Mn, Fe, Cu, and Zn observed in samples prepared with Svevo-HA. Gallic acid was identified as the major phenolic compound in all the tarhana samples for free fraction, while ferulic acid was determined as the major phenolic compound for its bound form. Supplementation of tarhana soups with heat-treated Svevo-HA flour increased the resistant starch content and decreased in vitro glycemic index value compared to soups prepared with conventional wheat flour. These findings highlight the potential of utilizing Svevo-HA flour to develop healthier versions of traditional foods.
Tekin Cakmak, Zeynep Hazal/0000-0002-3369-3128; Oruc, Sena/0000-0002-6052-109X; Sestili, Francesco/0000-0002-9653-8002;
Keywords: Resistant Starch; High-Amylose Wheat; Tarhana; Phenolics; Glycemic Index; RVA Soup Index